MODEL PERSAMAAN STRUKTURAL TINGKAT KEPUASAN MASYARAKAT TERHADAP KUALITAS PELAYANAN JALAN TOL BALI MANDARA - WIDHIANTARA, I PUTU AGUS; SUKARSA, I KOMANG GDE; N. KENCANA, I PUTU EKA (E-Jurnal Matematika; Vol 4 No 4 (2015), 2015)
The aim of th is research is to determine public satisfaction level for the quality of Bali Mandara Highway service and to determine the dominant variable influencing public satisfaction level. This research implemented by using Structural Equation Modeling Partial Least Square (SEM-PLS) and Servqual model. This research was conducted in Badung Regency in the period of March to June 2015. Data were collected by using questionnaires that were distributed directly to 150 users of respondents. The result shows that the public haven’t been satisfied with service quality provided by Jasamarga. Meanwhile the empathy, responsiveness and tangible are significantly influencing public satisfaction level to Bali Mandara Highway service quality. We also showed that empathy provide a dominant influence to public satisfaction level.
Keywords: Structural Equation Modeling Partial Least Square; service quality; public satisfaction level